1987
DOI: 10.1007/bf00329837
|View full text |Cite
|
Sign up to set email alerts
|

Shuttle transfer (or retrotransfer) of chromosomal markers mediated by plasmid pULB113

Abstract: The IncP1 plasmid pULB113 (RP4::miniMu) not only mediates the transfer of chromosomal markers in the classical direction (i.e. from the donor to the recipient cell) but also in the opposite direction (i.e. from the recipient bacterium to the donor). This phenomenon of retrotransfer was observed in homologous matings with Pseudomonas fluorescens, Alcaligenes eutrophus and Salmonella typhimurium. Retrotransconjugants could be discriminated from direct transconjugants by appropriate chromosomal and plasmid marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 14 publications
2
51
0
Order By: Relevance
“…The terms ' retrotransfer ', ' shuttle transfer ', plasmid-mediated ' gene capture ' or even a kind of bacterial ' hermaphroditism ', were used to describe a conjugational biparental event that led to the inheritance (capture) by the original host of a conjugative plasmid, of genetic traits (either chromosomal markers or plasmids) from the mating partner, free of conjugative plasmids. The frequency of this retrotransfer can be very high, being in some cases of the same order of magnitude as the frequencies observed for the transfer of genetic traits promoted in the canonical donor-recipient direction (Mergeay et al, 1987). Although the phenomenon was first observed and analysed in most detail for broad-host-range (BHR) IncP1 plasmids (Mergeay et al, 1987), it was also reported for other plasmids such as some IncN (pULG14) and IncM plasmids (R69.2) (Thiry et al, 1984 ;Mergeay et al, 1985), the IncF plasmid pDE-FL54 and the IncW plasmid pSa322 (Heinemann & Ankenbauer, 1993a), and for the catabolic IncP9 plasmid pWW0 (RamosGonzalez et al, 1994).…”
Section: Overview and General Definitionmentioning
confidence: 68%
See 4 more Smart Citations
“…The terms ' retrotransfer ', ' shuttle transfer ', plasmid-mediated ' gene capture ' or even a kind of bacterial ' hermaphroditism ', were used to describe a conjugational biparental event that led to the inheritance (capture) by the original host of a conjugative plasmid, of genetic traits (either chromosomal markers or plasmids) from the mating partner, free of conjugative plasmids. The frequency of this retrotransfer can be very high, being in some cases of the same order of magnitude as the frequencies observed for the transfer of genetic traits promoted in the canonical donor-recipient direction (Mergeay et al, 1987). Although the phenomenon was first observed and analysed in most detail for broad-host-range (BHR) IncP1 plasmids (Mergeay et al, 1987), it was also reported for other plasmids such as some IncN (pULG14) and IncM plasmids (R69.2) (Thiry et al, 1984 ;Mergeay et al, 1985), the IncF plasmid pDE-FL54 and the IncW plasmid pSa322 (Heinemann & Ankenbauer, 1993a), and for the catabolic IncP9 plasmid pWW0 (RamosGonzalez et al, 1994).…”
Section: Overview and General Definitionmentioning
confidence: 68%
“…The frequency of this retrotransfer can be very high, being in some cases of the same order of magnitude as the frequencies observed for the transfer of genetic traits promoted in the canonical donor-recipient direction (Mergeay et al, 1987). Although the phenomenon was first observed and analysed in most detail for broad-host-range (BHR) IncP1 plasmids (Mergeay et al, 1987), it was also reported for other plasmids such as some IncN (pULG14) and IncM plasmids (R69.2) (Thiry et al, 1984 ;Mergeay et al, 1985), the IncF plasmid pDE-FL54 and the IncW plasmid pSa322 (Heinemann & Ankenbauer, 1993a), and for the catabolic IncP9 plasmid pWW0 (RamosGonzalez et al, 1994). This capture of new genetic traits could thus be of great significance for the evolution of microbial communities, especially where stress is selecting rare events, yielding individual populations with new combinations of genes, which may allow better survival or more rapid growth.…”
Section: Overview and General Definitionmentioning
confidence: 68%
See 3 more Smart Citations